THE RHODES-LIVINGSTONE INSTITUTE AND INTERDISCIPLINARY RESEARCH IN NORTHERN RHODESIA (ZAMBIA), 1937-1964 (The Strategic Review for Southern Africa, 2020)
This article examines the rise of interdisciplinary research in Northern Rhodesia (colonial Zambia). It does this by exploring path breaking research conducted by the Rhodes-Livingstone Institute since its founding in 1937 up to the country's attainment of independence from Britain in 1964. The article argues that the rationale for the establishment of the research institute was due to the pressing need for knowledge owing to the emergence of social problems related to urban growth and labour migration by the 1930s. While not pretending to be an exhaustive survey of the work of the Rhodes-Livingstone Institute, the article notes that research outcomes from the Institute were utilised by the colonial administration and other stakeholders such as mining companies on the Copperbelt in order to understand the human situation in the country. By the 1950s, however, the Institute had become at variance with Government officials as the latter suspected many researchers of being sympathetic to the African political cause.